Morphology and dynamics of explosive vents through cohesive rock formations. Issue 6 (26th June 2014) - Galland, O.; Gisler, G. R.; Haug, Ø. T.
Abstract Shallow explosive volcanic processes, such as kimberlite volcanism and phreatomagmatic and phreatic activity, produce volcanic vents exhibiting a wide variety of morphologies, including vertical pipes and V‐shaped vents. In this study we report on experimental and numerical models designed to capture a range of vent morphologies in an eruptive system. Using dimensional analysis, we identified key governing dimensionless parameters, in particular the gravitational stress‐to‐fluid pressure ratio (Π2 = P/ρgh) and the fluid pressure‐to‐host rock strength ratio (Π3 = P/C). We used combined experimental and numerical models to test the effects of these parameters. The experiments were used to test the effect of Π2 on vent morphology and dynamics. A phase diagram demonstrates a separation between two distinct morphologies, with vertical structures occurring at high values of Π2 and diagonal ones at low values of Π2. The numerical simulations were used to test the effect of Π3 on vent morphology and dynamics. In the numerical models we see three distinct morphologies: vertical pipes are produced at high values of Π3, diagonal pipes at low values of Π3, and horizontal sills at intermediate values of Π3. Our results show that vertical pipes form by plasticity‐dominated yielding in high‐energy systems (high Π2 and Π3), whereas diagonal and horizontal vents dominantly form by fracturing in lower energy systems (low Π2 and Π3). Although our models are two‐dimensional, they suggest that circular pipes result from plastic yielding of the host rock in a high‐energy regime, whereas V‐shaped volcanic vents result from fracturing of the host rock in lower energy systems.